Hubungan Pemahaman Konsep dengan Berpikir Kritis pada Siswa Kelas VIII SMP Negeri Karoaipi - Sonya Liske Rumbewas; Nancy Susianna; Nerru Pranuta Murnaka (PT. Penerbit Tiga Mutiara, 2026)
Twenty-first-century science education requires students not only to master scientific concepts but also to possess critical thinking skills to analyze, evaluate, and solve problems logically. The reality in schools indicates that science learning is still frequently teacher-centered, resulting in students’ conceptual understanding and critical thinking skills not being optimally developed. This study aimed to determine the relationship between conceptual understanding and critical thinking skills among eighth-grade students of SMP Negeri Karoaipi on the topic of the human respiratory system. The study employed a quantitative approach with a correlational research design. The research sample consisted of 25 students selected through a convenience sampling technique. Data were collected using descriptive tests of conceptual understanding and critical thinking skills, while data analysis was conducted through descriptive statistics, normality testing, and simple linear regression analysis using SPSS. The findings revealed that students’ conceptual understanding was categorized as good, with a mean score of 77.36, while critical thinking skills were also categorized as good, with a mean score of 78.76. Regression analysis demonstrated a correlation coefficient of 0.045 and an R Square value of 0.002, indicating that the relationship between conceptual understanding and critical thinking skills was classified as very low. These findings suggest that critical thinking skills are influenced not only by conceptual mastery but also by learning strategies, problem-solving experiences, analytical activities, and student engagement during science learning. The novelty of this study lies in the empirical finding that strong conceptual mastery does not necessarily correspond to high critical thinking skills among junior high school students in rural schools, particularly on the topic of the human respiratory system.